Asbāb al-Nuzūl Skala Mikro Konteks Kesejarahan Al-Qur’an - Rifqi Muhammad Fatkhi (Refleksi: Jurnal Kajian Agama dan Filsafat, 2004)
The main concern of this study is how the Qur'an can address each of its readers in a current and contextual manner. So far, the Qur'an has been claimed as a religious text that remains relevant for all times and places (shāliḥ li kull zamān wa makān), whereas at the time of its revelation, the Qur'an (certain verses within it) had its own context (historical context). Hence, understanding the occasions of revelation (Asbāb al-Nuzūl) of the Qur'an becomes crucial in order to comprehend its verses.